2019
DOI: 10.1016/j.heliyon.2019.e02725
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt chromium-layered double hydroxide, α- and β- Co(OH)2 and amorphous Cr(OH)3: synthesis, modification and characterization

Abstract: Cobalt-chromium layered double hydroxide (CoCr LDH), α- and β- Co(OH)2 and amorphous Cr(OH)3 have been synthesized under different reaction conditions. The obtained CoCr LDH was modified by stearic acid (SA) and sodium stearate (SS). The obtained samples have been characterized by X-ray diffraction (XRD), Scanning electron microscope (SEM), Ultraviolet-visible- (UV-Vis), Fourier transform infrared- (FTIR) and Energy-dispersive X-ray- (EDX) spectroscopy. The influence of reaction conditions on product compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…[ 33 ] Although the particle size decreased with increasing basal spacing, the stability of the layers also weakened as the physical forces between the layers weakened. In the previous study, [ 4 ] the bandgap increased slightly (from 3.5 eV to 3.7 eV) with a sharp intercalation (from 7.366 Å to 25.214 Å). However, in the current study, although intercalation is not so high (from 7.00 Å to 7.62 Å), the bandgap is significantly reduced from 3.23 to 2.87 eV and from 3.25 to 2.82 eV for ZnAl‐LDH (ACTB) and ZnAl‐LDH/PVA, respectively.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…[ 33 ] Although the particle size decreased with increasing basal spacing, the stability of the layers also weakened as the physical forces between the layers weakened. In the previous study, [ 4 ] the bandgap increased slightly (from 3.5 eV to 3.7 eV) with a sharp intercalation (from 7.366 Å to 25.214 Å). However, in the current study, although intercalation is not so high (from 7.00 Å to 7.62 Å), the bandgap is significantly reduced from 3.23 to 2.87 eV and from 3.25 to 2.82 eV for ZnAl‐LDH (ACTB) and ZnAl‐LDH/PVA, respectively.…”
Section: Resultsmentioning
confidence: 78%
“…The average value of bandgap energy in LDHs was calculated to be $3-3,5 eV. [3,4] The band gap values indicate the gaps determined for all the semiconductors that exist in the visible-light region; hence, they can be applied in photocatalysis. [5] Zinc containing layered double hydroxides [6][7][8] oxides [9][10][11][12] sulfides [13][14][15] and other semiconductors [16] are very effective photocatalysts with unique optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…pH 9 and 10 are considered optimal for some metals (like Zn, Fe, Ni, Mn, etc.) [20]. Even extremely high concentration alkaline solution is used to obtain LDHs of some metals (like Ba, Ca) [21] because of the ion radii.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…[31][32][33][34] On the other hand, some studies have reported the formation of metal hydroxides as a byproduct in the synthesis of LDH. 35,36 Therefore, we expect that composite precursors of multi-metal hydroxides and LDHs are synthesized by the precipitation method and that calcination of the precursors at an appropriate temperature yields the composite of metal oxyhydroxide and spinel oxide, providing highly active bifunctional electrocatalysts (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%